PERBANDINGAN KADAR HEMOGLOBIN ANTARA ANAK YANG TERINFEKSI KECACINGAN DENGAN YANG TIDAK TERINFEKSI KECACINGAN PADA ANAK SEKOLAH DASAR NEGERI 048472 KUTAMBELIN DESA KUTAMBELIN KECAMATAN NAMAN TERAN - ALMAR ATUS SHOLIKAH; FANI ADE IRMA (LP2MTBM MAKARIOZ, 2023)
Soil Transmitted Helminths (STH) infection is a global problem, especially in developing countries. The most common worm infections are caused by Ascaris lumbricoides, Tricuris trichiura and Necator americanus and Ancylostoma duodenale. Children have a higher potential for worm infection due to their frequent contact with soil and lack of personal hygiene. Worm infections are also associated with reduce hemoglobin levels that cause anemia in children who are infected with worms. The incidence of STH contamination in North Sumatera is still quite high, especially in areas that that have the potential to be infeted with disease. To find out the comparison of hemoglobin levels in children who are infected with helminthiasis and those who are nor infected with worms at Elementary School 0488472 Kutambelin, Kutamelin Village, Naman Teran District. Analytical with cross sectional approach, sampling method using purposive sampling technique. The data in this study were obtained from primary data through examination of feces and blood directly on the sample. Data analysis using Fisher Exact Test. positive results of worms with no anemia as many as 9 children (15,8%) and anemia as many as 6 children (10,5%) Meanwhile, in children who did not have worms, 41 children (72,0%) were not anemic and 1 child (1,7%) had anemia. The results of the Fisher Exact Test obtained p value =0.001 (p value<0,05. There was a significant difference between hemogloin levels in children who were infected with worms and those who were not infected with worms at Kutambelin State Elementary School 048472 Kutambelin, Naman Teran District.